Elater ferrugineus and Osmoderma eremita, a regional survey and habitat requirements on different landscape scales - Forsmark, Benjamin (SLU/Horticulture (until 121231), 2012)
Habitat destruction and fragmentation is the primary cause behind loss of biodiversity. Population dynamics are affected by factors that act on different spatial scales. To direct nature management efforts, the impact of different factors and at which spatial scale they act needs to be taken into consideration. Elater ferrugineus and Osmoderma eremita are rare and threatened (red listed over their entire distribution range) saproxylic beetles associated with hollow deciduous trees. In the present thesis, these beetles have been surveyed using pheromone baited traps at 83 localities in Skåne. A multiscale analysis has been performed testing occupancy data for E. ferrugineus against densities of resources of different sorts of trees. This analysis stresses the requirements of E. ferrugineus for large non-fragmented areas with high densities of giant trees. Few localities match its requirements, and only eight resident populations appear to persist in Skåne. Four previously unknown localities for E. ferrugineus and two novel localities for O. eremita have been revealed in this thesis.